Фармакологічна корекція неускладнених гіпертензивних кризів антигіпертензивними препаратами для аплікаційного застосування (клініко-експериментальне дослідження) - Кечин, Ігор Леонідович; Kechin, I. L. (Запорізький державний медичний університет, 2009)
Дисертація присвячена дослідженню нового медикаментозного підходу до підвищення ефективності фармакотерапії неускладнених гіпертензивних кризів у хворих на АГ на тлі гіпертензивної ремодуляції «органів-мішеней» за рахунок використання трансмукозного шляху введення антигіпертензивних препаратів: натрію нітропрусиду, німодипіну й еналаприлу малеату для трансмукозного застосування. Вивчено експериментальну фармакодинаміку і фармакокінетику аплікаційних лікарських форм за умов експериментальної патології. Оцінено ефективність ніпруцелу у хворих на АГ зі схильністю до гіпертензивних кризів. Доведено переваги інтраназального застосування німодипіну у хворих на АГ із церебральними кризами на тлі гіпертензивної ремодуляції брахіоцефальних артерій. Обґрунтовано ефективність ректального застосування еналаприлу при кардіальних ГК на тлі гіпертензивної ремодуляції міокарду лівого шлуночка серця. Встановлено, що визначення цереброваскулярної реактивності за допомогою буккальної аплікації ніпруцелу дозволяє оптимізувати тактику терапії церебральних кризів. Доведена доцільність диференційного призначення трансмукозних лікарських форм вазодилататорів в терапії неускладнених гіпертензивних кризів: ніпруцелу буккально – при неускладнених кардіальних і церебральних кризах; гель-німодипіну інтраназально – при неускладнених церебральних кризах на тлі гіпертензивної ремодуляції екстрацеребральних артерій; еналаректу – при неускладнених кардіальних ГК на тлі гіпертензивної ремодуляції міокарду лівого шлуночка серця This work studies new pharmacologic approach of the correction of haemodynamic, methabolic and neurohumoral changes which occur during uncomplicated hypertensive crises in patients suffering from arterial hypertension (of the high risc group).This is done by introduction of the antihypertensive medications modified for transmucosal administration with proven clinical effect into the clinical practice. It is proven that sodium nitroprusside in buccal films regulates arterial tension during un-comlicated hypertensive crises within 24 hours from the beginning of a therapy, together with an adequate increase of the blood circulation in brain and kidneys. The research established that the determination of cerebrovascular reactivity by transbuccal introduction of sodium nitroprusside allows to optimise a therapy of un-complicated crises. The new approach of the therapy of uncomplicated hypertensive crises by auto controled hypotension using Sodium Nitroprusside in buccal films is offered. It is achieved due to the correction of the speed of absorbtion of films under independent control of blood pressure level. The study has proven expediency of Nimodipine applied intranasally to patients suffering from arterial hypertension with cerebral crises against a background of hypertensitive remodulation of brachiocephal arteries. The efficiency of rectal Enalapril applications at cardiac hypertensive crises with diastolic heart failure against a background of left ventricular myocardium remodelling has been proven. There is a well established proof of the expediency of differentiated administration of antihypertensives for transmucosal delivery for the therapy of uncomplicated hypertensive crises, namely: buccal Sodium Nitroprusside by uncomplicated cardiac and cerebral crises; applied intranasally Nimodipine (gel) by uncomplicated cerebral crises associated with hypertensive remodullation of extracerebral arterias; rectal suppositoria with Enalapril by uncomplicated cardiac crises against a background of hypertensive remodullation of myocardium of the left ventriculum.
The pharmacologic correction of the hypertensive crises by antihypertensive drugs of transmucosal administration (clinic-experimental research)
Keywords: артеріальна гіпертензія; гіпертензивні кризи; брахіоцефальні артерії; діастолічна дисфункція; arterial hypertension; hypertensive crises; diastolic disfunction of myocardium; brachiocephal arterias